Fluctuation of Patchouli Oil Price and Its Effect On Patchouli Aceh Production and Productivity - Yusnidar Yusnidar; Irma Susanti; Jamilah Jamilah; Ellyta Effendy; Romano Romano (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
The study aims to determine the price fluctuations and their effects on patchouli farm and patchouli oil production in Aceh Province. The Research Method used survey method with an explanatory research as an approach. The location of the study was conducted in Aceh Province, in Aceh Jaya Regency and Aceh Barat Regency. The fluctuations of patchouli oil price have an affect to the motivation of farmers in developing patchouli farming. Farmers in the study location tend to do patchouli farming when the price of patchouli oil is high, instead farmers do not do patchouli farming when the price of patchouli oil decreases. The fluctuations in patchouli oil prices determined by the quality of patchouli oil and market demand have a dominant influence on the development of production and the productivity of patchouli in Aceh. Standardization of patchouli oil quality at the agro-industry level will increase the price of patchouli oil at the farmers level and increase farmers' income. The price of patchouli oil fluctuates depends on Patchouli Alcohol (PA) levels. This is the main reason for traders at the district and provincial levels to reduce prices at the farm level. Aceh Patchouli has oil quality that qualified with basic export standards. But there is still a need for cultivation techniques and better application of refining technology to improve the quality of patchouli oil at the farmer level so that it can increase the price of patchouli oil at the farmer level while simultaneously increasing the income and welfare of farmers. The phenomenon of patchouli oil price fluctuations in high has an important role in the development of patchouli oil agro-industry.